2018
DOI: 10.1038/s41598-018-27653-1
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Application of Discrete Topographical Patterns Enhances Derivation of Functional Mesencephalic Dopaminergic Neurons from Human Induced Pluripotent Stem Cells

Abstract: Parkinson’s Disease is a progressive neurodegenerative disorder attributed to death of mesencephalic dopaminergic (DA) neurons. Pluripotent stem cells have great potential in the study for this late-onset disease, but acquirement of cells that are robust in quantity and quality is still technically demanding. Biophysical cues have been shown to direct stem cell fate, but the effect of different topographies in the lineage commitment and subsequent maturation stages of cells have been less examined. Using human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…In the present study, we showed that BCC surfaces with both 2 μm or 5 μm silica can promote enriched neuronal cultures. Our results expand the findings of previous studies that have used surface topography such as grantings, pillars and nanofiber scaffolds to support the generation of stem cell-derived neurons 13,1719 . In particular, some of the BCC surfaces are able to improve the generation of iNs with longer neurites and more complex branching, with the most prominent effect observed in BCC9 consisting of 5 μm silica and 100 nm carboxylated polystyrene, the smoothest and most hydrophobic surface among tested in this study.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In the present study, we showed that BCC surfaces with both 2 μm or 5 μm silica can promote enriched neuronal cultures. Our results expand the findings of previous studies that have used surface topography such as grantings, pillars and nanofiber scaffolds to support the generation of stem cell-derived neurons 13,1719 . In particular, some of the BCC surfaces are able to improve the generation of iNs with longer neurites and more complex branching, with the most prominent effect observed in BCC9 consisting of 5 μm silica and 100 nm carboxylated polystyrene, the smoothest and most hydrophobic surface among tested in this study.…”
Section: Discussionsupporting
confidence: 88%
“…For instance, Tan et al . found that grantings can aid early stages of neural differentiation, as they promote commitment into neural progenitors, whereas pillars increase branching and neuronal complexity that are more suitable for maturation 19 . Given that some of the BCCs (BCC9 and BCC13) promoted the generation of longer neurites and/or more complex neurite branching, these surfaces could be adapted to the late stages of existing neuronal differentiation protocols to promote neuronal maturation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when analyzing the expression of MAP2 and β-III tubulin, the neural differentiation of the iPSCs was higher on the patterned substrate compared to the control, a Matrigel-coated culture dish [43]. More recently, Tan et al used the sequential application of discrete topographical patterns on iPSCs to produce functional neurons [44]. A chemical induction was also necessary, but the effect of topographic cues was not negligible.…”
Section: Topography-guided Stem Cell Differentiationmentioning
confidence: 99%
“…In general, grooved topography can provide great insights into PSC fate choice and potentially expedite differentiation protocols. The MARC platform illustrates the importance of combining biophysical and biochemical cues, especially as exposure to topography induced a higher yield of functional and mature progeny within a short time frame as compared to flat substrates or standard directed differentiation protocols [ 230 , 235 ]. This is of extreme importance as current directed differentiation protocols for airway and lung epithelia require longer than 60 days of culture to achieve functional cell types [ 12 , 27 , 28 , 30 , 36 , 119 ].…”
Section: Opportunities To Exploit Mechanical Cues For Improving Direcmentioning
confidence: 99%